Clade-Specific Virulence Patterns of Mycobacterium tuberculosis Complex Strains in Human Primary Macrophages and Aerogenically Infected Mice - Norbert Reiling (American Society for Microbiology, 2013)
ABSTRACT In infection experiments with genetically distinct Mycobacterium tuberculosis complex (MTBC) strains, we identified clade-specific virulence patterns in human primary macrophages and in mice infected by the aerosol route, both reflecting relevant model systems. Exclusively human-adapted M. tuberculosis lineages, also termed clade I, comprising “modern” lineages, such as Beijing and Euro-American Haarlem strains, showed a significantly enhanced capability to grow compared to that of clade II strains, which include “ancient” lineages, such as, e.g., East African Indian or M. africanum strains. However, a simple correlation of inflammatory response profiles with strain virulence was not apparent. Overall, our data reveal three different pathogenic profiles: (i) strains of the Beijing lineage are characterized by low uptake, low cytokine induction, and a high replicative potential, (ii) strains of the Haarlem lineage by high uptake, high cytokine induction, and high growth rates, and (iii) EAI strains by low uptake, low cytokine induction, and a low replicative potential. Our findings have significant implications for our understanding of host-pathogen interaction and factors that modulate the outcomes of infections. Future studies addressing the underlying mechanisms and clinical implications need to take into account the diversity of both the pathogen and the host. IMPORTANCE Clinical strains of the Mycobacterium tuberculosis complex (MTBC) are genetically more diverse than previously anticipated. Our analysis of mycobacterial growth characteristics in primary human macrophages and aerogenically infected mice shows that the MTBC genetic differences translate into pathogenic differences in the interaction with the host. Our study reveals for the first time that “TB is not TB,” if put in plain terms. We are convinced that it is very unlikely that a single molecular mechanism may explain the observed effects. Our study refutes the hypothesis that there is a simple correlation between cytokine induction as a single functional parameter of host interaction and mycobacterial virulence. Instead, careful consideration of strain- and lineage-specific characteristics must guide our attempts to decipher what determines the pathological potential and thus the outcomes of infection with MTBC, one of the most important human pathogens.